Cambio de la virulencia de Hemileia vastatrix en progenies de Caturra X hibrido de Timor - Alvarado Alvarado, G.=700 1 Moreno Ruiz, L.G.
(En, Es)
ilus., 18 ref.
Keywords: COFFEA; ROYA; HEMILEIA VASTATRIX; RESISTENCIA GENETICA; VIRULENCIA; MORBOSIDAD; COLOMBIA